2017
DOI: 10.1038/ncomms14865
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in the intensity and relative toxicity of herbicide use

Abstract: Herbicide use is among the most criticized aspects of modern farming, especially as it relates to genetically engineered (GE) crops. Many previous analyses have used flawed metrics to evaluate herbicide intensity and toxicity trends. Here, I show that herbicide use intensity increased over the last 25 years in maize, cotton, rice and wheat. Although GE crops have been previously implicated in increasing herbicide use, herbicide increases were more rapid in non-GE crops. Even as herbicide use increased, chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 26 publications
(34 reference statements)
1
140
0
Order By: Relevance
“…From the perspective of pesticide applicators, the individuals more directly affected by these compounds, chronic toxicity is likely the more important of those two measures. Judged by its chronic toxicity to mammals, glyphosate is a relatively safe compound with lower levels of chronic toxicity than 90% of commonly used US herbicides [28]. The same analysis concluded that a reduction in glyphosate use or its discontinuation (as was recently proposed in Europe) would result in higher overall toxicity because it would likely be replaced by herbicides with higher toxicity.…”
Section: Human Healthmentioning
confidence: 81%
See 2 more Smart Citations
“…From the perspective of pesticide applicators, the individuals more directly affected by these compounds, chronic toxicity is likely the more important of those two measures. Judged by its chronic toxicity to mammals, glyphosate is a relatively safe compound with lower levels of chronic toxicity than 90% of commonly used US herbicides [28]. The same analysis concluded that a reduction in glyphosate use or its discontinuation (as was recently proposed in Europe) would result in higher overall toxicity because it would likely be replaced by herbicides with higher toxicity.…”
Section: Human Healthmentioning
confidence: 81%
“…First-generation GMOs have also served to shift the types of pesticide used, with the largest change being to increase the relative share of crop area produced using glyphosate. Evidence suggests that the switch from other herbicides to glyphosate has benefits for the health of growers even apart from any overall reduction in total amounts used [28].…”
Section: Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…US pesticide productivity has declined significantly (by more than 50%) over the past 30 years. In a study weighting herbicides by toxicity, herbicide use intensity was shown to increase for maize, cotton, rice and wheat over the last 25 years. Analyzing data from a large plot‐level, representative sample of US maize and soybean farmers from 1998 to 2011 provided ‘clear evidence of increasing herbicide use by GT variety adopters over time for both soybeans and maize, a finding that we attribute in part to the emergence of glyphosate weed resistance.’…”
Section: Recent Trends In Weed Managementmentioning
confidence: 99%
“…Considering oral rat LD 50 or 24-month oral rat no observable adverse effect level (NOAEL) values for acute or chronic toxicity for all herbicide active ingredients used, glyphosate was estimated in a study (Kniss, 2017) to contribute only 0.1, 0.3, and 3.5% of the chronic toxicity hazard in those crops, respectively, on the basis of the hazard quotient approach weighting the hazard (toxicity) with the areas and dosages applied. Nonetheless, this estimation considered a factor termed "area-treatment" (instead of the absolute amounts applied), solely the average exposure (vs. exposure dynamics), and only of the active ingredients.…”
Section: The Worldwide Market Of Glyphosatementioning
confidence: 99%